Impatiens pseudocitrina (Balsaminaceae), a new species from Arunachal Pradesh, Northeast India - Hareesh, Vadakkoot Sankaran; Gogoi, Rajib; Sabu, Mamiyil (Phytotaxa, 2016)
Impatiens pseudocitrina from Anjaw district, Arunachal Pradesh, North-East India, is newly described and illustrated. Detailed descriptions, distribution, and ecological information, along with colour photographs and key to the closely related species, are provided for identification of the species.